PERBANDINGAN KEMAMPUAN PEMAHAMAN MATEMATIS ANTARA SISWA YANG MENDAPATKAN STRATEGI CREATIVE PROBLEM SOLVING (CPS) DENGAN MODEL PEMBELAJARAN KONVENSIONAL - Tina Muliawati; Deddy Sofyan (Institut Pendidikan Indonesia, 2013)
ABSTRACT Most student is passive in the process learning of mathematics that leads to less in their creativity and achievement. Therefore, it needs an effort and innovatively learning of mathematics. As an alternative concerning such things one should develops learning of mathematics with “Creative Problem Solving (CPS)” approach. It is a learning approach which generates an activity between mathematics and students. Thus, it motivates them to solve the problem ununiquely with many stragies. As for which being experiment class is VII-D and VII-E. Class VII-D is gettingCreative Problem Solving (CPS) strategyand class VII-E is getting conventional teaching. For the experimental instrument was composed 6 essay.The gainof students mathematics understanding ability increases getting Creative Problem Solving (CPS) strategy is better than students who received conventional teaching.